Learning Organization through The Internalization of Transformational Leadership: A Study of An Indonesian School - Yoel Wibowo; Debora C Widjaja; Foedjiawati Foedjiawati (Journal of Leadership in Organizations, 2022)
Introduction: Conventional educational institutions around the world is currently hampered by a disruptive wave. Educational institutions, particularly schools, stress the need for controlled change to keep up with external uncontrolled changes. Learning Organization (LO) is very suitable to be implemented in every educational institution due to its conformity with continuous improvement and learning process. Objectives: This study aims to investigate the impact of Transformational Leadership (TL) on the creation of LO in a private school in Indonesia, especially among millennial employees working there. Novelty: This research is conducted in regard to the contextual (the implementation of TL in an educational institution and the inclusion of demographic factors) and the theoretical gap (detailed perspective on each of the dimensions of TL and the use of second-order modeling) left by previous research. Research Method: This study is designed as an applied research adopting mixed method approach to provide better triangulation and elaboration towards the case. Data is collected through survey and follow-up interviews towards the sample. Findings: This study points out that the implementation of TL has positive and significant impact on the creation of LO in the school, while the millennial age group does not moderate the impact of TL towards LO. In addition, Intellectual Stimulation is revealed to be the most reflective dimension of TL. Those results imply that the ability to correctly identify the contribution of each dimension in the leadership system will determine the success rate of an organization to implement changes.